Development of Digital-Based Marketing Strategies: A Case Study on Franchiseglobal.com - Kurnia Pangestu, Yudha; Hamdi, Edi; Indradewa, Rhian; Abadi , Ferryal (Syntax Corporation, 2024)
This study aims to analyze the digital-based marketing strategy implemented by FranchiseGlobal.com in order to increase exposure, market penetration, and brand awareness in the franchise industry. Using qualitative descriptive methods and a case study approach, this study explores digital marketing strategies that utilize big data, digital platforms, and social media to reach potential franchisees. Data were obtained through interviews, documentation, and direct observation of FranchiseGlobal.com's marketing activities. The results of the study indicate that the digital marketing strategy implemented by FranchiseGlobal.com, both in the short, medium, and long term, has succeeded in increasing the number of website visitors and brand awareness, although there are still challenges in expanding penetration into international markets, especially ASEAN. This study concludes that digital-based marketing is a crucial component in developing a franchise business more widely and effectively, and provides recommendations for optimizing the use of big data and technological innovation in future marketing strategies.